Voluntary International Mobility Lived in Laughter, Tears, and Resignification: Experiences of Brazilians Shared on YouTube Channels - Bueno, Janaina Maria; Domingues, Carlos Roberto; Vaz, Amanda Cristina Corrêa; Ferreira, Nicole Hage (Organizações & Sociedade, 2022)
Voluntary international mobility requires greater responsibility, given that there is no structure and organizational support for the challenge of living in another country. The aim of this study is to analyze the intercultural adaptation process of Brazilian immigrants and self-initiated expatriates in “off-axis” countries (less sought after/without a structured community of Brazilians) based on their reports and interactions on YouTube channels. The study employs a qualitative approach, with narrative research of four individuals. The data were collected between March and May of 2021 according to the following categories: intercultural adaptation; types of adaptation; structure and functioning of the channel. We confirmed the applicability of the theories of intercultural adaptation to analyze voluntary mobility, but with the need to consider specific aspects, such as advance adjustment actions, the influence of the channels on the focus and effort to adapt to the general environment and interact with the locals, and the emergence of individual aspects and behaviors (such as flexibility to change and self-knowledge), which were shown to be relevant for the intercultural adaptation process in voluntary mobility. As a theoretical contribution, it is understood that to use the theories about intercultural adaptation with the aim of analyzing voluntary mobility it is necessary to consider some specific aspects of this type of mobility while still in the country of origin, the weight and importance of each adaptation environment for the voluntary expatriate’s objective, and how much that experience is shared and exposed on different media with their respective impact on choices and (re)creation of meanings.